Modern Schools of Thought and Their Impact on the Sectarian Texts in the Islamic and Western Thought: Hermeneutics as an Example - Qatawneh, Mohamed Abdelhamid (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This study primarily seeks to find out the impact of modern schools of thought, their reading of revelation (wahy) and their attempt to turn the sacred constant to the human variable that allows absolute and infinite interpretation. This study also examines the theories, doctrines and philosophical foundations that were the reason for the existence of these schools. It also investigates the applications of these modern thoughts on doctrines. This study aims at demonstrating the methodological and scientific imbalance of these schools of thought and their projections on revelation. The study makes use of a comparative analytical approach that analyses and assesses these schools and approaches. The study concludes that Hermeneutics as a modern approach take on interpreting the holy text and in particular in regard to belief issues are far from the best practices of interpretation and that they distort the source of meaning and message.